Clinical Implications of Precordial ST‐segment Elevation in Acute Inferoposterior Myocardial Infarction Caused by Proximal Right Coronary Artery Occlusion - Jim, Man‐Hong (Clin Cardiol, 2007)
BACKGROUND: The clinical significance of inferior wall acute myocardial infarction (MI) with combined ST‐segment elevation in both anterior and inferior leads, compared with inferior leads alone, is unknown. HYPOTHESIS: Despite having more leads with precordial ST‐segment elevation, these patients may have a better outcome due to less posterior involvement, which tends to drag down the precordial ST‐segment. METHODS: A total of 158 postinferior MI patients with documented proximal right coronary artery occlusion were retrospectively studied. They were divided into three subgroups according to the magnitude of concurrent ST‐segment deviation in lead V2: Group A (n = 19) had ST‐segment elevation ≥ 2.0 mm; Group B (n = 74) had ST‐segment lay between + 2.0 mm and − 2.0 mm; and Group C (n = 65) had ST‐segment depression ≥ 2.0 mm. The clinical and electrocardiographic characteristics were then compared among these threes subgroups. RESULTS: The baseline demography, prevalence of risk factors, and treatment received were of no difference among the subgroups. However, Group A patients had significantly lower peak creatinine phosphokinase level and more preserved left ventricular function than Group B and C. Moreover, they had lower total sum of inferior ST‐segment magnitude, less ST‐segment depression in V4‐6, and more ST‐segment elevation in V(4R) than Group C. Group C patients had highest in‐hospital and one‐year mortality although it did not reach statistical significance. CONCLUSIONS: Precordial ST‐segment elevation in inferior wall acute MI was associated with smaller infarct size and better left ventricular function, probably secondary to occlusion of a less dominant RCA, which did not result in a significant posterior infarction. Copyright © 2007 Wiley Periodicals, Inc.